Feeding ecology of small deep-water lanternsharks (Etmopterus Spinax and Etmopteru Pusillus) off the Algarve Coast - Nuño Muñoz, Laura (2016)
Dissertação de Mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2016